TANTANGAN GURU DALAM PEMBELAJARAN BANGUN RUANG DI KELAS V SEKOLAH DASAR: KAJIAN DESKRIPTIF BERBASIS LITERATUR - Purba, Rani Natalia; Situmorang, Nia Diana; Sigalingging, Nursari Wahyuni; Pasaribu, Ernita (Jurnal Merah Putih Sekolah Dasar, 2025)
This study explores the various challenges encountered by teachers when teaching three-dimensional geometry to fifth-grade elementary students and outlines alternative solutions based on recent scholarly findings. Employing a qualitative descriptive approach, this study reviews theoretical perspectives and relevant documents to gain a comprehensive understanding of the issues. The results indicate that difficulties in teaching solid geometry arise from several interconnected factors, including students’ abilities, teachers’ preparedness, curriculum demands, availability of learning tools, and overall learning conditions. Limited spatial visualization skills, the scarcity of manipulatives, and the lack of diverse instructional approaches frequently hinder learning outcomes. Additionally, the demanding curriculum and inadequate learning environments further reduce instructional effectiveness. Recent research suggests that concrete manipulatives, real-world contextual learning, and technological tools such as GeoGebra 3D and Augmented Reality can significantly support students’ understanding. Strengthening teachers’ pedagogical skills through professional development is also highlighted as a crucial step. Implementing these strategies is expected to enhance students’ comprehension of solid geometry in a more meaningful and engaging manner.